2001
DOI: 10.1096/fj.00-0222com
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is promoted by the dsRNA‐activated factor (DRAF1) during viral infection independent of the action of interferon or p53

Abstract: An apoptotic cellular defense mechanism is triggered in response to viral dsRNA generated during the course of infection by many DNA and RNA viruses. We demonstrate that apoptosis induced by dsRNA or a paramyxovirus is independent of the action of interferon as it can proceed in a variety of cell lines and primary cells deficient in an interferon response. Initiation of apoptosis appears to be triggered by activation of a cellular transcription factor, the dsRNA-activated factor (DRAF1). DRAF1 is composed of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 59 publications
(140 reference statements)
4
61
2
Order By: Relevance
“…Even though it remains to be determined how different viruses or other factors influence apoptosis, our results demonstrate that although activation of NOXA and induction of apoptosis by SV occur concomitantly with production of type I IFNs, both apoptosis and induction of NOXA are unaffected by the presence of neutralizing anti-IFN a/b antibody, strongly suggesting that SV-induced apoptosis is IFN independent. These findings are in agreement with those of Weaver et al(2001), who demonstrated that apoptosis induced by dsRNA or a paramyxovirus is independent of the action of interferon as it occurs in a variety of cells defective in their ability to produce IFN.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Even though it remains to be determined how different viruses or other factors influence apoptosis, our results demonstrate that although activation of NOXA and induction of apoptosis by SV occur concomitantly with production of type I IFNs, both apoptosis and induction of NOXA are unaffected by the presence of neutralizing anti-IFN a/b antibody, strongly suggesting that SV-induced apoptosis is IFN independent. These findings are in agreement with those of Weaver et al(2001), who demonstrated that apoptosis induced by dsRNA or a paramyxovirus is independent of the action of interferon as it occurs in a variety of cells defective in their ability to produce IFN.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the finding that vesicular stomatis virus (VSV) infection can activate the p53 protein (Takaoka et al, 2003) suggests that p53 may play a role in virus-induced apoptosis, whereas on the other hand, destabilization of the p53 reported during ssRNA virus infection suggests that p53 degradation may facilitate apoptosis induced by ssRNA viruses (Marques et al, 2005). Both viral dsRNA and viral DNA have been shown, however, to induce apoptosis by mechanisms independent of both IFNs and p53 (Weaver et al, 2001). The observation that certain virus-induced transcription factors such as interferon regulatory factor 1 (IRF-1) and IRF-3, which activate transcription of both IFN and IFN-induced genes (ISG), exhibit proapoptotic activity (Taniguchi et al, 2001;Weaver et al, 2001) suggests that virus-induced apoptosis and the IFN activation pathways may share common components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated IRF-3/CREB-binding protein can directly bind to the promoter of ISG54, and the constitutively active IRF-3 mutant is sufficient to induce the ISG54 gene. 48 This is distinct from the contribution of IRF-3 to the expression of the IFN-b gene. The promoter region of IFN-b has been shown to bind several DNAbinding transcription factors that cooperate in an enhanceosome complex including IRF-3, NF-kB and AP-1 (c-jun:ATF2).…”
Section: Irf-3 Target Genesmentioning
confidence: 93%
“…However, many tumor cells do not display defects in the IFN system yet still are selectively destroyed by NDV. 19 Consequently, little is known of the molecular mechanisms responsible for the preferential lysis of tumor cells. 20 We recently reported the application of a lentogenic isolate of NDV-HUJ in a clinical trial with patients suffering from glioblastoma multiforme (GBM).…”
Section: Introductionmentioning
confidence: 99%